Development of The SEJATI Web-based Application as a Media for Promoting Adolescent Health to Prevent Stunting - Bayu Irianti; Masita Masita; Dede Gantini; Siti Saadah Mardiah (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2025)
Background: Adolescence is a vulnerable period, which is a period of physical (hormonal, primary, and secondary sexual state) and psychological (emotions, social relationships, and sexual behavior) with great curiosity. Both anemia in adolescents and early marriage are the main causes of stunting in babies. Adolescents who are anemic will result in anemia in pregnancy, either mothers with anemia during adolescence, or adolescents who experience unwanted pregnancy in a state of anemia (early marriage). Unlike the previous six applications, SEJATI was developed for adolescent boys and girls, providing a consultation page that is more developed than existing applications.Objectives: The objective of this study is to develop and assess the feasibility of SEJATI, a health promotion application for adolescents, using the SDLC prototype approach to provide improved consultation features and support adolescent healthMethods: This research method uses a qualitative method of SDLC (Software Development Life Cycle) system development, with a prototype approach, through seven stages of development, namely needs analysis, prototyping, prototype evaluation, system coding, system testing, system evaluation, and using the system.Results: SEJATI is worthy of being used as a health promotion medium for adolescents, with the results of material feasibility >75% both from the material, language, display and increasing motivation to read.Conclusion: The development of health promotion media using SDLC allows each prototype to be continued and developed so that it can be used optimally and as needed. SEJATI is developed with an SDLC approach, with 7 development steps with the assessment of 2 experts and 5 users as a feasibility test in a small scope. The test results are used as a refinement of SEJATI so that the final prototype can be tested for effectiveness.